Manajemen Sumberdaya Manusia Dalam Pengembangan Kompetensi Guru - Muhamad Ali Muhammad; Mohamad Erihadiana (Thawalib: Jurnal Kependidikan Islam, 2021)
In March 2020 the corona virus infected almost all countries in the world. The spread of this virus was declared a pandemic outbreak. New problems have arisen, ranging from economic, social to education problems. Simultaneously educational institutions are choosing online learning. This mini research aims to examine how to improve teacher competence during a pandemic, which is focused on the aspects of digitalization demands in the world of education. The review will focus on how the implementation of learning during the pandemic at Al-Ma'tuq Boarding School Sukabumi. The research method used in this research is qualitative research methods. The data collection technique is done through triangulation (combined), inductive / qualitative data analysis. Since the ministerial circular regarding learning during the pandemic was received, Al-Ma'tuq Boarding School immediately determined the strategy. Among them by hold training at the beginning of learning about technology, this proves that Al-Ma'tuq Boarding School continues to focus on developing competencies that teachers must have during this pandemic, including: (1) Competence in mastery of literacy and science and technology (2) Competence of classroom management skills (3) Communication and social competence. The existence of an online learning policy carried out by schools because of the covid outbreak, needs to be balanced with a deeper role for teachers. Teacher competence is demanded as a form of professionalism. However, it becomes a problem when the teacher lacks competence. So it is necessary to empower teachers by developing four main competencies that already exist to face today's online learning. With the development of competencies, it is expected to minimize existing problems, so that the learning process is better.